Clinical course of herpes virus skin diseases on the background of HIV - T.I. Liadova; D.M. Dorosh; O.V. Volobuieva; М.М. Popov; O.V. Martynenko; I.V. Kadyhrob; O.G. Sorokina (Medičnì Perspektivi, 2022)
Dermatological diseases are widespread among the HIV-infected population. Due to the continuing increase in the incidence of HIV, skin manifestations are becoming more common, especially herpes virus infections. Many of them are not unique in this group but the disease may not be typical, severe and systemic, which always complicates the diagnosis. Many studies demonstrate the specifics of the clinical course of HIV, in particular opportunistic infections, but a separate systematization of herpetic manifestations of HIV has not been conducted to date. On the other hand, the introduction of highly active antiretroviral therapy has been accompanied by some reduction in skin manifestations associated with HIV, and for clinicians the low efficacy of acyclovir in this category of patients, remains the main problem and therefore requires new approaches. The aim of this article was to study and compare the clinical course of herpes virus skin diseases on the background of HIV, taking into account the severity and stage of the underlying disease, based on the international classification of HIV adopted by the Centers for Disease Control (CDC). From September, 2018 to October, 2020, herpes was studied in 59 HIV patients and it was found that the nature of dermatological manifestations of herpes virus infections depends on the level of CD4+ cells. To expand drug provision, treat comorbid conditions and improve the quality of life of each patient, the dissertation, research «Clinical and immunological significance of IL-31 and melatonin in herpes virus skin diseases on the background of HIV infection and methods of their correction» is planned.